The world s worst weeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Of terrestrial weeds, 69% are broad-leaved weeds, 23% are grasses, 6% are sedges (leaved grasslike stems with small flowers), and 2% are ferns. The weeds below occur without exception in the subtropics and the tropics and are all found in upland...